Cladding of copper sheet on mild steel using friction stir welding - Mahto M.K.; Kumar A.; Raja A.R.; Vashista M.; Yusufzai M.Z.K. (My University, 2025)
Common welding processes that are used for cladding causes dilution and therefore, there is a need to explore new processes of cladding. In this work, friction stir welding process has been used to successfully clad 3 mm thick copper sheet on a 6 mm thick mild steel substrate. The process is different from lap welding, not only because of its intended purpose, but also because several FSW passes are needed to cover the entire surface of the substrate. After one FSW pass, successive passes were carried out to cover a wider width of the clad layer by offsetting the tool. Metallurgical examination of the transverse cross-section of cladded samples was carried out using optical microscopy, SEM–EDS, microhardness test, and XRD. Surface jetting type features, normally seen in explosive welding, were observed at the interface of the two materials. The average grain size of steel substrate below the clad layer for both single and triple passes showed refined grains with size of 3.9 µm and 4.2 µm respectively indicating an improvement of more than 60% over the base steel. Although there was plastic flow of material, the substrate material could not make to the top surface of the clad layer. XRD analysis confirmed no new phases were observed on the top surface of the clad layer after cladding. However, the interface region on the transverse cross-section confirmed the presence of Cu0.8Fe0.2 and Cu0.3Fe1.7 intermetallics. Microhardness for copper clad region remained nearly same across all the passes. However, for the steel substrate, higher hardness values were found near the stir zone due to grain refinement for single pass clad while for double and triple passes, a slight reduction was recorded possibly due to metal transfer across the boundary upon second and third passes. © 2021, The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature.